Uganda - Extension, Decentralization, and Village Participation - John Weetjens (World Bank, Washington, DC, 2012)
In Uganda, efforts to decentralize the management of the extension service and to launch the village participation in land development exercise have led to a number of issues, outcomes and expectations. This overview looks at what can be realistically expected from the extension service (in terms of contact with farmers), from decentralization (in terms of management improvement), and from the village participation exercise (in terms of grassroots empowerment).